A STUDY ON LOCUS OF CONTROL AND SELF CONFIDENCE OF HIGH SCHOOL STUDENTS - Vanaja, Y.; Geetha (International Journal of Research -GRANTHAALAYAH, 2017)
Locus of control refers to an individual’s perception of main causes of events in life. More simply, do you believe that your destiny is controlled by yourself that your destiny is controlled. Self - confidence is an essential part of humanity. Self - confidence is the internal sense, or belief that we can accomplish a variety of tasks or goals throughout life. Self - confidence is similar, but more related to believing we are generally competent in what we do, and that we deserve to be happy in life. A person with self-confidence generally likes herself, is willing to take risks to achieve her personal and professional goals, and thinks positively about the future. Self - confidence is something that you can build on your own! One of the major objectives of this study is to investigate self-confidence and locus of control in a cross-cultural context. Selected high school students from Government School, Private School and Government Aided School in Coimbatore District will be compared on self-confidence and locus of control. In addition, relationships of these psychological variables with academic achievement and with each other will also be examined. An examination of sex differences, as an independent variable, will also be investigated. The sample 300 high school students. Locus of control is another important and popular concept. Its construct has been the subject of psychological research since the late 1950s. Interest in the study started with Rotter’s (1966) monograph, which presented the concept of locus of control from social learning theory point of view.